Mixed Convection Boundary Layer Flow over a Horizontal Circular Cylinder in AL2O3-Ag/Water Hybrid Nanofluid with Viscous Dissipation - Elfiano, Eddy; Nik Mohd Izual, Nik Ibrahim; Muhammad Khairul Anuar, Mohamed (Semarak Ilmu Publishing, 2024)
This paper investigated the mathematical modelling for mixed convection boundary layer flow over a horizontal circular cylinder in hybrid nanofluid with viscous dissipation. The transformed partial differential equations (PDEs) are numerically solved using an implicit finite-difference approach known as the Keller-box method. The numerical solutions for the reduced Nusselt number, , local skin friction coefficient, , temperature profile, and velocity profiles are found and graphically presented in detail. Effects of the Eckert number, Richardson number and nanoparticle volume fraction are all examined and explained. It is found that the increase of volume fraction of nano material in nanofluid has increased the value of skin friction coefficient. The low density of nano oxides such as alumina in hybrid nanofluids also contribute to reduce friction between fluid and body surface. Based on numerical analysis, the combination of nanoparticles in the form of hybrid nanofluid may reduce skin friction phenomena while sustaining heat transfer characteristics comparable to nanofluid. The results in this paper are original and will assist researchers working in the field of boundary layer flow. It can also be utilised as a reference in experimental studies to reduce operating costs.